1980
DOI: 10.1128/iai.27.2.355-363.1980
|View full text |Cite
|
Sign up to set email alerts
|

Complement-dependent antiviral monospecific antibody-mediated lysis of murine cells coated with Sendai virus or its envelope component

Abstract: Complement-dependent antiviral antibody-mediated lysis of murine cells coated with Sendai virus or its envelope component (P815 mastocytoma cells and L929 cells) was studied with antiviral monospecific sera (anti-F and anti-HN sera). Three types of interactions different in terms of susceptibility to complement-dependent antibody-mediated lysis were distinguished: (i) fusion-positive Sendai viruses induced the susceptibility with both anti-F and anti-HN sera; (ii) fusion-negative envelope particles with F prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1980
1980
1983
1983

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Figure 11 also illustrates possible fracture planes of cell associations with LLC-SV and TE. We could not find any morphological evidence of envelope fusion with LLC-SV or TE, which is consistent with the finding that they have no hemolytic or cell fusion activity (9,13,30).…”
Section: Envelope Fusion With Repsupporting
confidence: 90%
See 2 more Smart Citations
“…Figure 11 also illustrates possible fracture planes of cell associations with LLC-SV and TE. We could not find any morphological evidence of envelope fusion with LLC-SV or TE, which is consistent with the finding that they have no hemolytic or cell fusion activity (9,13,30).…”
Section: Envelope Fusion With Repsupporting
confidence: 90%
“…In a previous report (13), we showed that TE-coated but not LLC-SV-coated murine cells were susceptible to complement-dependent antibody-mediated cytolysis. The present results suggest the formation of a no more stable membrane association with TE than with LLC-SV.…”
Section: Cell Association With Llc-sv and Tementioning
confidence: 68%
See 1 more Smart Citation
“…Non-infectious Sendai virus was grown in LLC-MK2 cells, an established line of rhesus monkey kidney cells, which had been infected with egg-grown infectious virus. This virus (LLC-SV) had a log ratio of infectivity to hemagglutination units of about 2, in contrast to infectious virus which had a ratio of 6 to 7, and it contained predominantly precursor protein Fo (9).…”
Section: Methodsmentioning
confidence: 95%
“…Hale et al (6), using MDBK cell-grown noninfectious Sendai virus, reported that virusattached P815 and EIA cells absorbed anti-Sendai virus antibodies as efficiently as did trypsinactivated infectious virus-coated cells. However, noninfectious Sendai virus-coated cells were found to be resistant to anti-Sendai cytotoxic T lymphocyte-mediated lysis (4,5) and also, to complement-dependent antibody-mediated cytolysis (9). Therefore, it was interesting to elucidate the ultrastructure of these nonfunctional virus-cell associations.…”
mentioning
confidence: 99%